2020
DOI: 10.1371/journal.pone.0228555
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial usage at a large teaching hospital in Lusaka, Zambia

Abstract: Antimicrobial resistance is a growing global health concern. Antimicrobial stewardship (AMS) curbs resistance rates by encouraging rational antimicrobial use. However, data on antimicrobial stewardship in developing countries is scarce. The objective of this study was to characterize antimicrobial use at the University Teaching Hospital (UTH) in Lusaka, Zambia as a guiding step in the development of an AMS program. This was a cross-sectional, observational study evaluating antimicrobial appropriateness and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
4
19
1
Order By: Relevance
“…In our study, cephalosporins were the third most utilized group considering ATC level 3 as opposed to the study in Zambia (32) and Pakistan (33), where there was high use of cephalosporin prompting ASP measures in that settings.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…In our study, cephalosporins were the third most utilized group considering ATC level 3 as opposed to the study in Zambia (32) and Pakistan (33), where there was high use of cephalosporin prompting ASP measures in that settings.…”
Section: Resultscontrasting
confidence: 72%
“…Frequent use of cephalosporins was observed in Ethiopia (21). High use of metronidazole was also noted in a study in Karthoum (22) and Lusaka Zambia (32) and Pakistan (33).…”
Section: Resultsmentioning
confidence: 73%
“…While we could not test for broad-spectrum beta-lactamase production, the high rates of resistance to 3 rd generation cephalosporins, 41.4% susceptibility of E. coli and 15.6% susceptibility of K. pneumomiae to ceftriaxone, respectively, indicate this is common. This is not entirely unexpected as 3 rd generation cephalosporins are the most commonly utilized antibiotics at UTH, driving the development of ESBL-producing organisms [27]. Studies from SSA reveal high rates of ESBL production [16,28] or resistance to 3 rd generation cephalosporins [2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a study conducted at the UTH reported a 53.7% antibiotic prescription rate [ 64 ], clearly surpassing the 30% rate recommended by the WHO [ 65 ]. Most serious bacterial infections among UTH inpatients are treated with third-generation cephalosporins (e.g., cefotaxime) [ 66 ], while quinolones (e.g., ciprofloxacin) are commonly used for outpatient infections [ 64 ]. Our results show that nearly 90% of cefotaxime-resistant strains were also resistant to quinolones.…”
Section: Discussionmentioning
confidence: 99%